STUDI PREVALENSI DAN KAJIAN FAKTOR RISIKO HIPERTENSI PADALANSIA DI DESA TAMBAKSARI - BANYUMAS - Reni Dwi Setyaningsih; Pramesti Dewi; Made Suandika (Universitas Muhammadiyah Semarang, 2014)
Hypertension is one of the non-communicable diseases (PTM), which is referred to asthe sillent killer, is a condition characterized by systolic blood pressure values and ≥140 mmHgor diastolic blood pressure ≥90 mmHg. WHO estimates that in 2020 a group of elderly agegroups are susceptible to hypertension. In addition to age, the incidence of hypertension isthought to relate to the lifestyles that include smoking, coffee consumption, salt intake, thepattern of other activities, stress and obesity / body mass index. The results of the surveyconducted in the village of Tambaksari, of the total population, the elderly dominate nearly 30percent of the population. Based on the results of elderly health screening conducted throughfour posyandu elderly suggests that of ± 300 elderly people who come to posyandu activeseniors, nearly 30 percent identified as having high blood pressure through consistentmeasurement for monitoring twice. The study aims to find the e prevalence of hypertensionand risk factors associated with hypertension in the elderly. Some things that will be analyzedin this study were age, gender, family history of hypertension, smoking habits, coffeeconsumption, body mass index and consumption of salty foods. This study was anobservational analytic study using a cross sectional design. The population of this study were allactive elderly come to the neighborhood health center during 2014, amounting to 192 seniors.Sampling was done by total sampling on all active elderly visits to neighborhood health center.The data will be analyzed with the chi square test at 95% significance level. The resultsshowed that the factor of family history of hypertension and salty food consumption habitsshowed a significant association with the incidence of hypertension with the magnitude of riskfactors (RP) are 1.3 and 1.4 respectively.Keywords : Hypertension, risk factor, elderly